Prospective multicentre study of risk factors associated with delayed healing of recurrent duodenal ulcers (RUDER). RUDER Study Group. Issue 10 (October 1993) - Armstrong, D; Arnold, R; Classen, M; Fischer, M; Goebell, H; Blum, A L
Abstract : Risk factors for delayed duodenal ulcer healing during treatment with ranitidine (300 mg daily) were examined in a multicentre German study of 1923 patients with endoscopically proved, recurrent duodenal ulceration. Healing rates, per protocol, were 39.5% at two weeks, 70.9% at four weeks, and 93.2% at eight weeks. Prospective testing of five, predefined risk factors indicated that smoking (p = 0.0039) was associated with a decreased healing rate at two weeks. Frequent prior recurrence (p = 0.464), a heavy physical workload (p = 0.145), and psychological stress (p = 0.062) were not associated with a decreased healing rate and there were too few patients at risk to allow assessment of the effect of regular NSAID intake. Exploratory analysis identified prior slow healing, a large ulcer, multiple ulcers, and prior ulcer complications, in addition to smoking, as markers of slow healing. In the absence of these risk factors, the mean healing time was 3.3 weeks (95% confidence interval 3.0, 3.5), rising to 3.7 weeks (3.5, 3.9) for one, 4.4 weeks (4.1, 4.7) for two, and 5.1 weeks (4.5, 5.6) for three to five risk factors. Delayed duodenal ulcer healing is associated with multiple factors whose effect is cumulative; for patients with two or more of five easily identified risk factors, more than four weeks' treatment with a histamine H2 receptor antagonist is required to achieve ulcer healing.